Towards the comprehension of Human Resources Technical Training in Health: an experience of the research line of pedagogy and education in health from the HRTCH (Human Resources Training Centre in Health) - Díaz Reina, Gabriel Augusto
This article from the research line of pedagogy and education in health, pertaining to the HSRG (Health Services Research Group) of the HRTCH from SENA, presents in a descriptive manner advantages of the goals achieved in the multi centre investigation to identify and analyse the quantitative and qualitative offer in training technician workers in health from the countries members of the INEHT (International Network of Education of Health Technicians). Subsequently, a current normative frame is presented for the human resources training in health in Colombia and some considerations in relation to health worker´s technical training.